Implementation of Islamic Education Curriculum in Early Childhood Education: Challenges and Solutions - Luthfiah Luthfiah (Al-Banat: Journal of Early Childhood Islamic Education, 2025)
The implementation of the Islamic education curriculum in Early Childhood Education (ECE) is a strategic effort to instill character and Islamic values from an early age. The background of this study is rooted in the importance of internalizing Islamic values in accordance with the developmental stages of children. The objective of this research is to analyze the challenges in applying the Islamic education curriculum in ECE institutions and to identify strategic solutions that can be implemented. This study employs a qualitative approach using literature review and field observations in several Islamic-based ECE institutions. The results reveal that the main challenges include limited teacher competence in comprehensively understanding the Islamic curriculum, lack of contextual learning media, and parental resistance to religious-based pedagogical approaches. Proposed solutions include improving teacher capacity through continuous training, developing creative learning media based on Islamic values, and involving parents in the learning process through Islamic parenting programs. The conclusion of this study emphasizes the importance of collaboration between educational institutions, parents, and the government in successfully implementing the Islamic education curriculum in early childhood settings.